MEMBANGUN NEGERI DARI KAMPUS: SINERGI GENBI SULAWESI SELATAN DALAM PENINGKATAN KAPASITAS SDM DAN SOSIALISASI KEBANKSENTRALAN - Pratama, Muh Adjie Putra; Saputra, Ridwan; A Dagong, Muhammad Ihsan (Jurnal Abdi Insani, 2025)
The Generasi Baru Indonesia (GenBI) South Sulawesi community service program aims to improve financial literacy, entrepreneurship, health, environment, and education through various activities involving students, students, MSMEs, and local communities. Some of the main programs carried out include QRISpeak for Student and GenBI QRISpreneur Fest for financial literacy and digitization of MSMEs, GenBI Skizo(Friend)ia and GenBI Traveller in the field of mental health and health checks in remote areas, Mangrove Rehabilitation and Planting and INTUISI for environmental conservation, as well as GenBI Inclusive and GenBI Leadership with Lontara in improving basic literacy and preserving local culture. The program implementation method includes needs observation to understand the existing problems, interactive education that actively involves participants in learning, training and mentoring to improve practical skills, and social campaigns to expand the reach and impact of the program. The results of the program show a significant increase in participants' understanding and engagement. Indicators of success include the increased active participation of the community, the formation of a mentored community, and the application of the knowledge provided in daily life. In addition, this program also succeeded in creating a space for students to contribute directly to social development through various forms of sustainable service. With this achievement, the GenBI South Sulawesi community service program is expected to become a sustainable community empowerment model and make a real contribution to strengthening community capacity in various sectors. The sustainability of this program is an important aspect in encouraging inclusive social and economic development based on collaboration between students, communities and other stakeholders.